Laser-induced thermography: An effective detection approach for multiple-type defects of printed circuit boards (PCBs) multilayer complex structure. (January 2023) - Wang, Fei; Zhou, Yihao; Zhang, Xuan; Li, Zhijie; Weng, Jiexin; Qiang, Guiyan; Chen, Mingjun; Wang, Yang; Yue, Honghao; Liu, Junyan
Highlights: Laser-induced thermography was utilized to detect the multiple-type defects of rigid or rigid flexible PCBs. The thermal-wave diffusion model for four-layer PCBs simulation structure induced by sinusoidal modulation laser was built. The phase realizes the effective detection of PCBs delamination defects with a depth of 1.2 mm and microporous defects with a depth of 400 μm. Abstract: Due to the multilayer complex structure characteristics of printed circuit boards (PCBs), multiple types of defects (Such as delamination, debonding, and breakdown damage) are likely to occur during processing and use, which affects the performance of the entire electronic component. In the present study, infrared thermography was employed to detect the multiple-type defects of PCBs. Initially, the thermal-wave diffusion model for a four-layer PCBs simulation structure induced by a sinusoidal modulation laser was built. Meanwhile, the finite element methods were utilized to solve the thermal-wave mathematical model and analyze the behavior of thermal-wave diffusion. Furthermore, a four-layer copper-clad laminate structure with flat bottom holes (FBHs) simulated delaminate defect was designed and manufactured. Finally, laser-induced lock-in thermography was adopted to detect the multiple types of actual defects (breakdown damage, delamination defect, fold defect, and micropore) of rigid or rigid-flexible PCBs. The phase characteristic image realizes the effective detection of PCBs delamination defects with a depth of 1.2 mm and microporous defects with a depth of 400 μm. The experimental results demonstrated that laser-induced thermography is suitable to detect the multiple-type defects of PCBs.